2022
DOI: 10.3389/fimmu.2022.845301
|View full text |Cite
|
Sign up to set email alerts
|

Weak Expression of Terminal Complement in Active Antibody-Mediated Rejection of the Kidney

Abstract: BackgroundThe role of the complement system in antibody-mediated rejection (ABMR) is insufficiently understood. We aimed to investigate the role of local and systemic complement activation in active (aABMR). We quantified complement activation markers, C3, C3d, and C5b-9 in plasma of aABMR, and acute T-cell mediated rejection (aTCMR), and non-rejection kidney transplant recipients. Intra-renal complement markers were analyzed as C4d, C3d, C5b-9, and CD59 deposition. We examined in vitro complement activation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Treating ECs with PL‐C—and thus removing the natural complement defense—creates a rather artificial situation. However, literature indicate reduced expression of the membrane bound complement regulatory proteins CD46, CD55 and CD59 on rejected renal grafts 34,35 . Literature showed that reduced CD55 expression and increased sensitivity to complement deposition differ per cell type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treating ECs with PL‐C—and thus removing the natural complement defense—creates a rather artificial situation. However, literature indicate reduced expression of the membrane bound complement regulatory proteins CD46, CD55 and CD59 on rejected renal grafts 34,35 . Literature showed that reduced CD55 expression and increased sensitivity to complement deposition differ per cell type.…”
Section: Discussionmentioning
confidence: 99%
“…However, literature indicate reduced expression of the membrane bound complement regulatory proteins CD46, CD55 and CD59 on rejected renal grafts. 34 , 35 Literature showed that reduced CD55 expression and increased sensitivity to complement deposition differ per cell type. Downregulation of CD55 did not significantly alter C3 deposition on HUVEC and human NT2‐N neurons, 36 , 37 while loss of CD55 on glomeruli in kidney biopsies and on murine vascular endothelial cells coincides with increased C3 deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have specifically looked at peritubular capillaries as major targets of AMR and as sites of complement fixation. Tiller et al [6] found in graft biopsies that C3d and C4d deposition discriminated AMR from TCMR, particularly, C3d in glomeruli and peritubular capillaries. C5b-9 was minimally expressed and did not distinguish the groups.…”
Section: Pathologic Features and Outcomesmentioning
confidence: 99%
“…10,11 In addition, it has been suggested that especially complement binding DSAs are pathogenic. Although biopsies of rejected grafts showed positive C4d deposition, [12][13][14] convincing evidence has emerged that antibody-mediated rejection could also occur in absence of positive C4d staining. 15,16 Although studies showed that the specificity of pre-transplant DSAs (Class I and/or Class II) did not clearly impact long-term transplant outcome, 17 there is also research showing that in particular persistent Class II DSAs are associated with inferior graft survival.…”
Section: Introductionmentioning
confidence: 99%